Pornografi dalam Balutan Film Bertema Horor Mistik di Indonesia - Herawati, Erni (Humaniora, 2011)
The film industry in Indonesia has been through ups and downs. As an industry, thus there are usual things the film creators done to take financial benefit from the film industry. Some researches show that messages brought by mass communication media is no more that political and economic efforts from media to get much more benefits. Therefore, it is acknowledged that Indonesian films lately put horror and mystic theme beneath in order to get closer with Indonesia culture as the consumers. However, it is issued when the mystic theme influenced along with pornography. Ethics development efforts and law enforcement must be the continuous material to discuss the problem solving.